MANAJEMEN SARANA DAN PRASARANA TK NEGERI PEMBINA SAMBAS - Ningsih Ningsih; H.M. Chiar; Wahyudi Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstract Management of educational facilities and infrastructures is needed in order to implement quality education process, effective and efficient. Research questions are directed to: how the planning, effectiveness of use, care, supervision and barriers in the procurement of facilities and infrastructure in TK Negeri Pembina Sambas. To disclose the researchers using qualitative research methods. The process of collecting data was obtained using observations, interviews, and document studies. The results revealed that the planning was done based on needs analysis, effectiveness and efficiency based on schedule and rules implemented with group learning to move space according to centers and learning with Beyond Centers and Circle Times (BCCT) model. Recommendation; That the concept of facilities and infrastructure management in TK Negeri Pembina Sambas has a tendency to lead to the concept of learning Beyond Centers and Circle Times (BCCT). In order to be effective and efficient recruitment of personnel in charge of maintaining and maintaining facilities and infrastructure so that no double job occurs. Teachers focus on learners and educational services to children not neglected. Keywords: Management, Facilities, Infrastructure